2018
DOI: 10.1128/iai.00096-18
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Component Signaling System VraSR ss Is Critical for Multidrug Resistance and Full Virulence in Streptococcus suis Serotype 2

Abstract: has received increasing attention for its involvement in severe human infections worldwide as well as in multidrug resistance. Two-component signaling systems (TCSSs) play important roles in bacterial adaptation to various environmental stimuli. In this study, we identified a novel TCSS located in serotype 2 (SS2), designated VraSR, which is involved in bacterial pathogenicity and susceptibility to antimicrobials. Our data demonstrated that the gene, located upstream of , shared the same promoter with the TCSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Macrophage phagocytosis activates TCS genes. The genome of the ZY05719 strain encodes 15 putative TCSs, among which RevS, Salk/SalR, CovR, CiaRH, Ihk/Irr, VirR/VirS, NisK/NisR, 1910HK/RR, and VraSR SS have already been identified to contribute to SS2 virulence (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). To explore the potential roles of the remaining six uncharacterized TCSs in bacterial pathogenicity, murine macrophage-like RAW264.7 cells were applied to coincubate with the SS2 strain ZY05719.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Macrophage phagocytosis activates TCS genes. The genome of the ZY05719 strain encodes 15 putative TCSs, among which RevS, Salk/SalR, CovR, CiaRH, Ihk/Irr, VirR/VirS, NisK/NisR, 1910HK/RR, and VraSR SS have already been identified to contribute to SS2 virulence (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). To explore the potential roles of the remaining six uncharacterized TCSs in bacterial pathogenicity, murine macrophage-like RAW264.7 cells were applied to coincubate with the SS2 strain ZY05719.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the S. suis transcriptional landscape has revealed that genes involved in CPS biosynthesis were upregulated in blood (45). Nevertheless, S. suis CPS-deficient mutants have been reported to adhere to epithelial cells better than the encapsulated parental strain (20,46,47), as CPS might cover adhesins on the bacterial surface (48). Therefore, it has been proposed that S. suis downregulates expression of the capsule for increased adhesion to epithelial cells during the early steps of infection, whereas it upregulates capsule production after entering the bloodstream to counter phagocytosis (49).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations